Depth in arrangements: Dehn–Sommerville–Euler relations with applications - Biswas, Ranita; Cultrera Di Montesano, Sebastiano; Edelsbrunner, Herbert; Saghafian, Morteza (Journal of Applied and Computational Topology)
The depth of a cell in an arrangement of n (non-vertical) great-spheres in Sd is the number of great-spheres that pass above the cell. We prove Euler-type relations, which imply extensions of the classic Dehn–Sommerville relations for convex polytopes to sublevel sets of the depth function, and we use the relations to extend the expressions for the number of faces of neighborly polytopes to the number of cells of levels in neighborly arrangements.

Hippocampal cholecystokinin-expressing interneurons regulate temporal coding and contextual learning - Rangel Guerrero, Dámaris K; Balueva, Kira; Barayeu, Uladzislau; Baracskay, Peter; Gridchyn, Igor; Nardin, Michele; Roth, Chiara N; Wulff, Peer; Csicsvari, Jozsef L (Neuron)
Cholecystokinin-expressing interneurons (CCKIs) are hypothesized to shape pyramidal cell-firing patterns and regulate network oscillations and related network state transitions. To directly probe their role in the CA1 region, we silenced their activity using optogenetic and chemogenetic tools in mice. Opto-tagged CCKIs revealed a heterogeneous population, and their optogenetic silencing triggered wide disinhibitory network changes affecting both pyramidal cells and other interneurons. CCKI silencing enhanced pyramidal cell burst firing and altered the temporal coding of place cells: theta phase precession was disrupted, whereas sequence reactivation was enhanced. Chemogenetic CCKI silencing did not alter the acquisition of spatial reference memories on the Morris water maze but enhanced the recall of contextual fear memories and enabled selective recall when similar environments were tested. This work suggests the key involvement of CCKIs in the control of place-cell temporal coding and the formation of contextual memories.

Shared behavioural impairments in visual perception and place avoidance across different autism models are driven by periaqueductal grey hypoexcitability in Setd5 haploinsufficient mice - Burnett, Laura; Koppensteiner, Peter; Symonova, Olga; Masson, Tomas; Vega Zuniga, Tomas A; Contreras, Ximena; Rülicke, Thomas; Shigemoto, Ryuichi; Novarino, Gaia; Jösch, Maximilian A
Relevant information about the data can be found in the 'Readme_Data.txt' file. A previous version of the publication can be found on BioRxiv: https://www.biorxiv.org/content/10.1101/2022.10.11.511691v4 and published in Plos Biology (2024)
Keywords: ASD; periaqueductal gray; perception; behavior; potassium channels

Deuteration of proteins boosted by cell lysates: High-resolution amide and Ha magic-angle-spinning (MAS) NMR without the reprotonation bottleneck - Napoli, Federico; Guan, Jia-Ying; Arnaud, Charles-Adrien; Macek, Pavel; Fraga, Hugo; Breyton, Cécile; Schanda, Paul (Magnetic Resonance)
Amide-proton-detected magic-angle-spinning NMR of deuterated proteins has become a main technique in NMR-based structural biology. In standard deuteration protocols that rely on D2O-based culture media, non-exchangeable amide sites remain deuterated, making these sites unobservable. Here we demonstrate that proteins produced with a H2O-based culture medium doped with deuterated cell lysate allow scientists to overcome this “reprotonation bottleneck” while retaining a high level of deuteration (ca. 80 %) and narrow linewidths. We quantified coherence lifetimes of several proteins prepared with this labeling pattern over a range of magic-angle-spinning (MAS) frequencies (40–100 kHz). We demonstrate that under commonly used conditions (50–60 kHz MAS), the amide 1H linewidths with our labeling approach are comparable to those of perdeuterated proteins and better than those of protonated samples at 100 kHz. For three proteins in the 33–50 kDa size range, many previously unobserved amides become visible. We report how to prepare the deuterated cell lysate for our approach from fractions of perdeuterated cultures which are usually discarded, and we show that such media can be used identically to commercial media. The residual protonation of Hα sites allows for well-resolved Hα-detected spectra and Hα resonance assignment, exemplified by the de novo assignment of 168 Hα sites in a 39 kDa protein. The approach based on this H2O/cell-lysate deuteration and MAS frequencies compatible with 1.3 or 1.9 mm rotors presents a strong sensitivity benefit over 0.7 mm 100 kHz MAS experiments.

Neurochemistry and circuit organization of the lateral spiriform nucleus of birds: A uniquely nonmammalian direct pathway component of the basal ganglia - Reiner, Anton; Medina, Loreta; Abellan, Antonio; Deng, Yunping; Toledo, Claudio A.B.; Luksch, Harald; Vega Zuniga, Tomas A; Riley, Nell B.; Hodos, William; Karten, Harvey J. (Journal of Comparative Neurology)
We used diverse methods to characterize the role of avian lateral spiriform nucleus (SpL) in basal ganglia motor function. Connectivity analysis showed that SpL receives input from globus pallidus (GP), and the intrapeduncular nucleus (INP) located ventromedial to GP, whose neurons express numerous striatal markers. SpL-projecting GP neurons were large and aspiny, while SpL-projecting INP neurons were medium sized and spiny. Connectivity analysis further showed that SpL receives inputs from subthalamic nucleus (STN) and substantia nigra pars reticulata (SNr), and that the SNr also receives inputs from GP, INP, and STN. Neurochemical analysis showed that SpL neurons express ENK, GAD, and a variety of pallidal neuron markers, and receive GABAergic terminals, some of which also contain DARPP32, consistent with GP pallidal and INP striatal inputs. Connectivity and neurochemical analysis showed that the SpL input to tectum prominently ends on GABAA receptor-enriched tectobulbar neurons. Behavioral studies showed that lesions of SpL impair visuomotor behaviors involving tracking and pecking moving targets. Our results suggest that SpL modulates brainstem-projecting tectobulbar neurons in a manner comparable to the demonstrated influence of GP internus on motor thalamus and of SNr on tectobulbar neurons in mammals. Given published data in amphibians and reptiles, it seems likely the SpL circuit represents a major direct pathway-type circuit by which the basal ganglia exerts its motor influence in nonmammalian tetrapods. The present studies also show that avian striatum is divided into three spatially segregated territories with differing connectivity, a medial striato-nigral territory, a dorsolateral striato-GP territory, and the ventrolateral INP motor territory.

EIGER. V. Characterizing the host galaxies of luminous quasars at z ≳ 6 - Yue, Minghao; Eilers, Anna Christina; Simcoe, Robert A.; Mackenzie, Ruari; Matthee, Jorryt J; Kashino, Daichi; Bordoloi, Rongmon; Lilly, Simon J.; Naidu, Rohan P. (Astrophysical Journal)
We report JWST/NIRCam measurements of quasar host galaxy emissions and supermassive black hole (SMBH) masses for six quasars at 5.9 < z < 7.1 in the Emission-line galaxies and Intergalactic Gas in the Epoch of Reionization (EIGER) project. We obtain deep NIRCam imaging in the F115W, F200W, and F356W bands, as well as F356W grism spectroscopy of the quasars. We use bright unsaturated stars to construct models of the point-spread functions (PSFs) and estimate the errors of these PSFs. We then measure or constrain the fluxes and morphology of the quasar host galaxies by fitting the quasar images as a point source plus an exponential disk. We successfully detect the host galaxies of three quasars, which have host-to-quasar-flux ratios of ∼1%–5%. Spectral energy distribution fitting suggests that these quasar host galaxies have stellar masses of M* ≳ 1010M⊙. For quasars with host galaxy nondetections, we estimate the upper limits of their stellar masses. We use the grism spectra to measure the Hβ line profile and the continuum luminosity, then estimate the SMBH masses for the quasars. Our results indicate that the positive relation between SMBH masses and host galaxy stellar masses already exists at redshift z ≳ 6. The quasars in our sample show a high BH-to-stellar-mass ratio of MBH/M* ∼ 0.15, which is about ∼2 dex higher than local relations. We find that selection effects only contribute partially to the high MBH/M* ratios of high-redshift quasars. This result hints at a possible redshift evolution of the MBH–M* relation.

Optical Shubnikov-de Haas oscillations in two-dimensional electron systems - Savchenko, M. L.; Gospodarič, J.; Shuvaev, A.; Dmitriev, I. A.; Dziom, Vlad; Dobretsova, A. A.; Mikhailov, N. N.; Kvon, Z. D.; Pimenov, A. (Physical Review Research)
We report on dynamic Shubnikov–de Haas (SdH) oscillations that are measured in the optical response, subterahertz transmittance of two-dimensional systems, and reveal two distinct types of oscillation nodes: “universal” nodes at integer ratios of radiation and cyclotron frequencies and “tunable” nodes at positions sensitive to all parameters of the structure. The nodes in both real and imaginary parts of the measured complex transmittance are analyzed using a dynamic version of the static Lifshitz-Kosevich formula. These results demonstrate that the node structure of the dynamic SdH oscillations provides an all-optical access to quantization- and interaction-induced renormalization effects, in addition to parameters one can obtain from the static SdH oscillations.

Quantum-informed recursive optimization algorithms - Finžgar, Jernej Rudi; Kerschbaumer, Aron; Schuetz, Martin J.A.; Mendl, Christian B.; Katzgraber, Helmut G. (PRX Quantum)
We propose and implement a family of quantum-informed recursive optimization (QIRO) algorithms for combinatorial optimization problems. Our approach leverages quantum resources to obtain information that is used in problem-specific classical reduction steps that recursively simplify the problem. These reduction steps address the limitations of the quantum component (e.g., locality) and ensure solution feasibility in constrained optimization problems. Additionally, we use backtracking techniques to further improve the performance of the algorithm without increasing the requirements on the quantum hardware. We showcase the capabilities of our approach by informing QIRO with correlations from classical simulations of shallow circuits of the quantum approximate optimization algorithm, solving instances of maximum independent set and maximum satisfiability problems with hundreds of variables. We also demonstrate how QIRO can be deployed on a neutral atom quantum processor to find large independent sets of graphs. In summary, our scheme achieves results comparable to classical heuristics even with relatively weak quantum resources. Furthermore, enhancing the quality of these quantum resources improves the performance of the algorithms. Notably, the modular nature of QIRO offers various avenues for modifications, positioning our work as a template for a broader class of hybrid quantum-classical algorithms for combinatorial optimization.

Integrin β1–mediated mast cell immune-surveillance of blood vessel content - Link, Kristina; Muhandes, Lina; Polikarpova, Anastasia; Lämmermann, Tim; Sixt, Michael K; Fässler, Reinhard; Roers, Axel (Journal of Allergy and Clinical Immunology)
Background: IgE-mediated degranulation of mast cells (MCs) provides rapid protection against environmental hazards, including animal venoms. A fraction of tissue-resident MCs intimately associates with blood vessels. These perivascular MCs were reported to extend projections into the vessel lumen and to be the first MCs to acquire intravenously injected IgE, suggesting that IgE loading of MCs depends on their vascular association. Objective: We sought to elucidate the molecular basis of the MC–blood vessel interaction and to determine its relevance for IgE-mediated immune responses. Methods: We selectively inactivated the Itgb1 gene, encoding the β1 chain of integrin adhesion molecules (ITGB1), in MCs by conditional gene targeting in mice. We analyzed skin MCs for blood vessel association, surface IgE density, and capability to bind circulating antibody specific for MC surface molecules, as well as in vivo responses to antigen administered via different routes. Results: Lack of ITGB1 expression severely compromised MC–blood vessel association. ITGB1-deficient MCs showed normal densities of surface IgE but reduced binding of intravenously injected antibodies. While their capacity to degranulate in response to IgE ligation in vivo was unimpaired, anaphylactic responses to antigen circulating in the vasculature were largely abolished. Conclusions: ITGB1-mediated association of MCs with blood vessels is key for MC immune surveillance of blood vessel content, but is dispensable for slow steady-state loading of endogenous IgE onto tissue-resident MCs.

Integral points on singular del Pezzo surfaces - Derenthal, Ulrich; Wilsch, Florian Alexander (Journal of the Institute of Mathematics of Jussieu)
In order to study integral points of bounded log-anticanonical height on weak del Pezzo surfaces, we classify weak del Pezzo pairs. As a representative example, we consider a quartic del Pezzo surface of singularity type A1 + A3 and prove an analogue of Manin's conjecture for integral points with respect to its singularities and its lines.
Keywords: Integral points; del Pezzo surface; universal torsor; Manin’s conjecture

Every diffeomorphism is a total renormalization of a close to identity map - Berger, Pierre; Gourmelon, Nicolaz; Helfter, Mathieu (Inventiones mathematicae)
For any 1 ≤ r ≤ ∞, we show that every diffeomorphism of a manifold of the form R/Z × M is a total renormalization of a Cr-close to identity map. In other words, for every diffeomorphism f of R/Z×M, there exists a map g arbitrarily close to identity such that the first return map of g to a domain is conjugate to f and moreover the orbit of this domain is equal to R/Z×M. This enables us to localize near the identity the existence of many properties in dynamical systems, such as being Bernoulli for a smooth volume form.

Light-mediated interconversion between a foldamer and a self-replicator - Jin, Yulong; Mandal, Pradeep K; Wu, Juntian; Kiani, Armin; Zhao, Rui; Huc, Ivan; Otto, Sijbren (Journal of the American Chemical Society)
Self-replicating molecules and well-defined folded macromolecules are of great significance in the emergence and evolution of life. How they may interconnect and affect each other remains largely elusive. Here, we demonstrate an abiotic system where a single building block can oligomerize to yield either a self-replicating molecule or a foldamer. Specifically, agitation of a disulfide-based dynamic combinatorial library at moderately elevated pH channels it selectively into a self-replicating hexamer assembled into fibers, after passing through a period where a 15-subunit macrocyclic foldamer existed transiently. Without mechanoagitation or at lower pH, the formation of hexamer fiber is suppressed, resulting in the accumulation of the 15mer foldamer. Foldamer and self-replicator can be interconverted in response to external stimuli, including agitation and a change in pH. Furthermore, upon the addition of a photoacid, the pH of the medium can be controlled by irradiation, driving the switching between replicator and foldamer and allowing a dissipative out-of-equilibrium state to be accessed, using light as a source of energy.

Simultaneous formation of a foldamer and a self-replicator by out-of-equilibrium dynamic covalent chemistry - Sood, Ankush; Mandal, Pradeep K; Ottelé, Jim; Wu, Juntian; Eleveld, Marcel; Hatai, Joydev; Pappas, Charalampos G.; Huc, Ivan; Otto, Sijbren (Journal of the American Chemical Society)
Systems chemistry has emerged as a useful paradigm to access structures and phenomena typically exhibited by living systems, including complex molecular systems such as self-replicators and foldamers. As we progress further toward the noncovalent synthesis of life-like systems, and eventually life itself, it is necessary to gain control over assembly pathways. Dissipative chemical fueling has enabled access to stable populations of (self-assembled) structures that would normally form only transiently. Here, we report a synthetic dynamic combinatorial library, made from a single structurally simple building block, from which a self-replicator and a foldamer can emerge along two distinct and competing pathways through an inter- or intramolecular assembly process, respectively. A fueled chemical reaction cycle is then set up to generate the foldamer transiently, in the presence of the self-replicator. The partitioning of the building block between the folding and self-replication pathways and the duration of the fueled reaction cycles are controlled by adjusting the amount of the chemical fuel. An out-of-equilibrium steady state involving the two assemblies could also be achieved by using a continuous stirred tank reactor with inflow and outflow of material. This work connects the domains of folding and self-replication in synthetic systems through dissipative out-of-equilibrium chemistry. It demonstrates that foldamers and self-replicators, formed from the same building block, can stably coexist if the system is continuously supplied with energy, while at equilibrium, the Gibbs phase rule prohibits such coexistence.
Keywords: Fibers; Foldamers; Macrocycles; Monomers; Peptides; Proteins

Interrogating the potential of helical aromatic foldamers for protein recognition - Kwon, Sunbum; Morozov, Vasily; Wang, Lingfei; Mandal, Pradeep K; Chaignepain, Stéphane; Douat, Céline; Huc, Ivan (Organic & Biomolecular Chemistry)
A biotinylated helical aromatic oligoamide foldamer equivalent in size to a 24mer peptide was designed without any prejudice other than to display various polar and hydrophobic side chains at its surface. It was synthesized on solid phase, its P- and M-helical conformers were separated by HPLC on a chiral stationary phase, and the solid state structure of a non-biotinylated analogue was elucidated by X-ray crystallography. Pull-down experiments from a yeast cell lysate using the foldamer as a bait followed by proteomic analysis revealed potential protein binding partners. Three of these proteins were recombinantly expressed. Biolayer interferometry showed submicromolar binding demonstrating the potential of a given foldamer to have affinity for certain proteins in the absence of design considerations. Yet, binding selectivity was low in all three cases since both P- and M-conformers bound to the proteins with similar affinities.

UNCOVER: Candidate red active galactic nuclei at 3 < z < 7 with JWST and ALMA - Labbe, Ivo; Greene, Jenny E.; Bezanson, Rachel; Fujimoto, Seiji; Furtak, Lukas J.; Goulding, Andy D.; Matthee, Jorryt J; Naidu, Rohan P.; Oesch, Pascal A.; Atek, Hakim; Brammer, Gabriel; Chemerynska, Iryna; et al. (The Astrophysical Journal)
The James Webb Space Telescope (JWST) is revolutionizing our knowledge of z > 5 galaxies and their actively accreting black holes. Using the JWST Cycle 1 Treasury program Ultradeep NIRSpec and NIRCam Observations before the Epoch of Reionization (UNCOVER) in the lensing field A2744, we report the identification of a sample of little red dots at 3 < zphot < 7 that likely contain highly reddened accreting supermassive black holes. Using a NIRCam-only selection to F444W < 27.7 mag, we find 26 sources over the ∼45 arcmin^2 field that are blue in F115W − F200W ∼ 0 (or βUV ∼ –2.0 for fλ ∝ λ^β), red in F200W − F444W = 1−4 (βopt ∼ +2.0), and are dominated by a point-source-like central component. Of the 20 sources with deep Atacama Large Millimeter/submillimeter Array (ALMA) 1.2 mm coverage, none are detected individually or in a stack. For the majority of the sample, spectral energy distribution fits to the JWST+ALMA observations prefer models with hot dust rather than obscured star formation to reproduce the red NIRCam colors and ALMA 1.2 mm nondetections. While compact dusty star formation cannot be ruled out, the combination of extremely small sizes (〈re〉 ≈ 50 pc after correction for magnification), red rest-frame optical slopes, and hot dust can be explained by reddened broad-line active galactic nuclei (AGNs). Our targets have faint M1450 ≈ −14 to −18 mag but inferred bolometric luminosities of Lbol = 10^43–10^46 erg s^−1, reflecting their obscured nature. If the candidates are confirmed as AGNs with upcoming UNCOVER spectroscopy, then we have found an abundant population of reddened luminous AGNs that are at least ten times more numerous than UV-luminous AGNs at the same intrinsic bolometric luminosity.

archaeal_membranes : code and examples - Santana de Freitas Amaral, Miguel
No description provided.

Raw data to "MAS NMR experiments of corynebacterial cell walls: complementary 1H- and CPMAS CryoProbe-enhanced 13C-detected experiments" - Schanda, Paul
Bacterial cell walls are gigadalton-large cross-linked polymers with a wide range of motional amplitudes, including rather rigid as well as highly flexible parts. Magic-angle spinning NMR is a powerful method to obtain atomic-level information about intact cell walls. Here we investigate sensitivity and information content of different homonuclear 13C-13C and heteronuclear H-N, H-C and N-C correlation experiments. We demonstrate that a CPMAS CryoProbe yields ca. 8-fold increased signal-to-noise over a room-temperature probe, or a ca. 3-4-fold larger per-mass sensitivity. The increased sensitivity allowed to obtain high-resolution spectra even on intact bacteria. Moreover, we compare resolution and sensitivity of 1H MAS experiments obtained at 100 kHz vs. 55 kHz. Our study provides useful hints for choosing experiments to extract atomic-level details on cell-wall samples.
Keywords: nuclear magnetic resonance; NMR; cellwall; structural biology; spectroscopy

Dynamics of a rank-one multiplicative perturbation of a unitary matrix - Dubach, Guillaume; Reker, Jana (Random Matrices: Theory and Applications)
We provide a dynamical study of a model of multiplicative perturbation of a unitary matrix introduced by Fyodorov. In particular, we identify a flow of deterministic domains that bound the spectrum with high probability, separating the outlier from the typical eigenvalues at all sub-critical timescales. These results are obtained under generic assumptions on U that hold for a variety of unitary random matrix models.

The translocation of a chloride channel from the Golgi to the plasma membrane helps plants adapt to salt stress - Rajappa, Sivamathini; Krishnamurthy, Pannaga; Huang, Hua; Yu, Dejie; Friml, Jiří; Xu, Jian; Kumar, Prakash P. (Nature Communications)
A key mechanism employed by plants to adapt to salinity stress involves maintaining ion homeostasis via the actions of ion transporters. While the function of cation transporters in maintaining ion homeostasis in plants has been extensively studied, little is known about the roles of their anion counterparts in this process. Here, we describe a mechanism of salt adaptation in plants. We characterized the chloride channel (CLC) gene AtCLCf, whose expression is regulated by WRKY transcription factor under salt stress in Arabidopsis thaliana. Loss-of-function atclcf seedlings show increased sensitivity to salt, whereas AtCLCf overexpression confers enhanced resistance to salt stress. Salt stress induces the translocation of GFP-AtCLCf fusion protein to the plasma membrane (PM). Blocking AtCLCf translocation using the exocytosis inhibitor brefeldin-A or mutating the small GTPase gene AtRABA1b/BEX5 (RAS GENES FROM RAT BRAINA1b homolog) increases salt sensitivity in plants. Electrophysiology and liposome-based assays confirm the Cl−/H+ antiport function of AtCLCf. Therefore, we have uncovered a mechanism of plant adaptation to salt stress involving the NaCl-induced translocation of AtCLCf to the PM, thus facilitating Cl− removal at the roots, and increasing the plant’s salinity tolerance.

Optimal lower bound on eigenvector overlaps for non-Hermitian random matrices - Cipolloni, Giorgio; Erdös, László; Henheik, Sven Joscha; Schröder, Dominik J (Journal of Functional Analysis)
We consider large non-Hermitian NxN matrices with an additive independent, identically distributed (i.i.d.) noise for each matrix elements. We show that already a small noise of variance 1/N completely thermalises the bulk singular vectors, in particular they satisfy the strong form of Quantum Unique Ergodicity (QUE) with an optimal speed of convergence. In physics terms, we thus extend the Eigenstate Thermalisation Hypothesis, formulated originally by Deutsch [34] and proven for Wigner matrices in [23], to arbitrary non-Hermitian matrices with an i.i.d. noise. As a consequence we obtain an optimal lower bound on the diagonal overlaps of the corresponding non-Hermitian eigenvectors. This quantity, also known as the (square of the) eigenvalue condition number measuring the sensitivity of the eigenvalue to small perturbations, has notoriously escaped rigorous treatment beyond the explicitly computable Ginibre ensemble apart from the very recent upper bounds given in [7] and [45]. As a key tool, we develop a new systematic decomposition of general observables in random matrix theory that governs the size of products of resolvents with deterministic matrices in between.